Coats disease in female population: A comparison of clinical presentation and outcomes - Piquin, Gwendoline; Chapron, Thibaut; Abdelmassih, Youssef; Martin, Gilles; Edelson, Catherine; Caputo, Georges; Metge, Florence (Frontiers in Medicine, 2022)
Purpose: To compare clinical characteristics at presentation and outcomes of Coats’ disease between females and males. Methods: In this retrospective, consecutive case series we included all children diagnosed with Coats’ disease in a single tertiary referral center. Initial clinical presentation, treatment and outcomes were collected. Results: A total of 158 children were included, of whom 29 (18.3%) were females and 11 (6.9%) had bilateral involvement. Age at diagnosis and disease stage were similar between females and males. Females tended to have a worse visual acuity at diagnosis (p = 0.05) and more bilateral involvement (p < .001). Visual and anatomical outcomes after treatment were similar between genders. Conclusion: Female patients with Coats’ disease have more bilateral involvement and tended to have worse visual acuity at presentation. Clinical presentation and outcomes seem to be similar between genders.